Hubungan Motivasi Wanita Usia Subur Dengan Keikutsertaan Dalam Pemeriksaan Infeksi Visual Asam Asetat Di Puskesmas Klari - Komyani; Masluroh (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Objective: IVA Test is used to detect cervical cancer. The IVA test procedure is to assess the cervix that has been given 3-5% acetic acid via inspection. After the cervix is ​​reviewed using acetic acid, a color change will occur on the cervix which can be assessed directly and read as a normal or abnormal condition. All women of childbearing age should carry out an IVA test to detect cervical cancer early. The better the motivation of women of childbearing age, the more women of childbearing age will carry out early detection of cervical cancer using the IVA test method. Methods: This research uses quantitative analytical research. With a cross sectional study approach. The population in this study were all women of childbearing age in the working area of ​​Klari Community Health Center, namely 63 people. Sampling technique The sampling technique used was accidental sampling. Inclusion Criteria: a) Have had sexual relations. b) Not menstruating. c) Not currently pregnant. d) 24 hours before do not have sexual relations. e) Age 18-45 years. f) Willing to be a respondent. Exclusion Criteria: a) Not willing to be a respondent. b) Have a history of hereditary disease. c) Aged <18 years Results: Of the 39 respondents, based on WUS motivation, there were 17 (43.6%) respondents with strong motivation and took part in the IVA examination and there were 2 (5.1%) respondents with strong motivation but did not take part in the IVA examination. Based on moderate motivation, there was 1 (2.6%) respondent with moderate motivation and took part in the IVA examination and there were 6 (15.4%) respondents with medium motivation but did not take part in the IVA examination. Meanwhile, based on weak motivation, there was 1 (2.6%) respondent with weak motivation but who participated in the IVA examination and there were 12 (30.8%) respondents with weak motivation who also did not participate in the IVA examination. Conclusion: Based on the results of the Chi-Square statistical test, a ρ value of 0.000 was obtained, meaning that there is a relationship between the motivation of women of childbearing age and participation in the acetic acid visual infection examination.